Piezoresistive Properties of 2D based Nanocomposites for Strain Sensing Applications - Garcia, James (Trinity College Dublin. School of Physics. Discipline of Physics, 2023)
The superlative piezoresistive properties of nanomaterials and their composites have attracted great interest in the area of strain sensing. The field has grown exponentially over the past decade, benefiting from the maturity of liquid phase processing of layered crystals and other nanomaterials. The development and application of nanomaterial strain sensors face a number of challenges that must be overcome, if they are to proliferate the next generation of technologies. This work looks to address some of the issues around the stability and sensitivity of the resistance-strain response in piezoresistive nanocomposites, hoping to further optimise strain sensor development. Piezoresistive nanocomposites show exceptional promise due to their robust, stretchable nature coupled with a high strain sensitivity. A caveat is that the electrical properties of nanocomposites are known to suffer from hysteresis effects and a high strain rate dependence. In an effort to suppress these undesirable effects, a highly strain-sensitive nanocomposite known as G-putty was fabricated into nanocomposite thin films through various printing techniques. The thin films show a marked increase (?106) in conductivity compared to the bulk due to a partial phase segregation of the network. Despite this morphological change, the G-putty thin films maintain a high strain sensitivity. In addition, the preparation of thin films on PDMS substrates frustrates the viscoelastic relaxation observed in bulk G-putty, leading to a significant reduction in the resistance hysteresis and strain rate dependence. The properties of the thin films make them promising candidates for integration in strain sensing devices, with a number of use cases demonstrated. Following on from the work on G-putty thin films it became clear that a strong relationship exists between the piezoresistive and conductive properties of nanocomposites. Surprisingly the mechanisms underlying this behaviour are not well understood and development has been hampered by the absence of physical models that could be used to fit data and optimize sensor performance. To address this, a model was developed relating strain sensitivity to the filler loading and nanocomposite conductivity. The model was used to fit experimental and literature data, which outputs figures a merit to characterise the piezoresistive response. Importantly the model also provides insight into the piezoresistive mechanism, demonstrating that the effect of strain on the filler network structure dictates the resistance response. While the initial work of this thesis focuses on polymer nanocomposites, the properties of 2D materials offer an opportunity to study mixtures insulating, semiconducting and conducting phases. Such mixtures are much more difficult to obtain in polymer nanocomposites and thus lie relatively unstudied. The piezoresistive properties of nanocomposite films comprised solely of 2 dimensional nanosheets where explored, displaying a wide range of percolative properties on account of the diverse properties offered by 2D materials. This rich set of behaviours leads to a unique set piezoresistive properties depending on the nanocomposite type. In each case, percolation theory was used to develop models for nanocomposite strain sensitivity as a function of both conductor volume fraction and nanocomposite conductivity. This approach yields equations which can be used to fully describe the experimental data. These results open the way to the future design of improved strain sensing systems.
APPROVED
Keywords: Strain Sensing; 2D Materials; Percolation; Piezoresistivity